Effect of Rearing Program, Body Conformation and Protein Level of Breeder Feed on Broiler Breeder Hen Reproductive Performance - England, J.A.; Moyle, J.R.; Yoho, D.E.; Bramwell, R.K.; Ekmay, R.D.; Kriseldi, R.; Coon , C.N. (International Journal of Poultry Science, 2014)
The effect of pullet growth curve on body conformation and subsequent reproductive performance and effect of breeder feed protein level on reproductive performance was determined. The cost effectiveness of the different programs was evaluated. Cobb 700e pullets were reared from day of age in floor pens. Each pen was assigned to one of two growth curves from 16 weeks of age to housing at 21 weeks of age. One growth curve followed a standard (SD) body weight curve and a second followed a lighter (LI) body weight curve. At 23 weeks of age, half of the hens from each of the growth curves were assigned to one of two breeder diets. Half of the hens were fed a low (LO)-protein (14%) breeder diet and half were fed a higher (HI)-protein breeder diet (16%) during the production phase. Pullet growth curve significantly affected body weight through 30 weeks of age. The protein level of the breeder feed significantly affected body weight at 35 and 40 weeks of age. Pullet growth curve affected body conformation, but did not affect age of first egg. Pullet growth curve did not affect egg weight. Protein level of the breeder feed significantly affected egg weight; hens fed the HI-protein diet laid heavier eggs. Egg production was not affected by pullet rearing growth curve (p = 0.0845) or protein level (p = 0.7348) of the breeder feed. Feeding a LO-protein diet resulted in feed cost savings. The feed cost of SD reared hens fed LO-protein diet was 0.03227 per hen less than for those fed HI-protein diets. The feed cost of LI reared hens fed LO-protein diet was 0.3616 per hen less than for those fed HI-protein diet.